1983
DOI: 10.1002/ana.410130410
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal IgG bands in cerebrospinal fluid in various neurological diseases

Abstract: We studied the frequency of oligoclonal immunoglobulin G bands in the cerebrospinal fluid (CSF) of patients with various neurological diseases. We used a micromethod employing sodium dodecyl sulfate polyacrylamide gel electrophoresis that required only 50 microliters of unconcentrated CSF. Oligoclonal bands were detected in the CSF of 95% of the patients with multiple sclerosis, 90% with subacute sclerosing panencephalitis, and 100% with herpes simplex encephalitis, but less frequently in other central nervous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
4

Year Published

1984
1984
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 30 publications
2
41
1
4
Order By: Relevance
“…This is in agreement with a few previous studies on PDD [3][4][5][6], but contradictory to several oth ers [7][8][9][10][11][12][13]. The frequency of intrathecal IgG synthesis in PDD patients is rather small, but was revealed in the present study probably because of the large number of patients in comparison with other studies.…”
Section: Intrathecal Synthesis O F Igg In Pddsupporting
confidence: 38%
See 1 more Smart Citation
“…This is in agreement with a few previous studies on PDD [3][4][5][6], but contradictory to several oth ers [7][8][9][10][11][12][13]. The frequency of intrathecal IgG synthesis in PDD patients is rather small, but was revealed in the present study probably because of the large number of patients in comparison with other studies.…”
Section: Intrathecal Synthesis O F Igg In Pddsupporting
confidence: 38%
“…Primary degenerative dementia (PDD; Alzheimer's disease) is a brain disorder charcterized by progressive impairment of memory and other cognitive functions in combination with loss of nerve cells, presence of neuritic plaques and neurofibrillary tangles [1], The etiology of PDD is unknown, but several studies have suggested that dysfunction of the immune system may play a role in the etiology of the disease [for a review see 2], This sugges tion has been supported by the occurrence of oligoclonal immunoglobulin G (IgG) bands in the cerebrospinal fluid (CSF) of patients with PDD [3][4][5][6], However, sev eral other studies have yielded contradictory results, i.e., no evidence of intrathecal IgG synthesis in PDD patients [7][8][9][10][11][12][13], This contradiction induced us to carry out the present study, using a large group of well-defined PDD patients and a large group of healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…Polypeptide bands in the IgG region appear to be of central origin and represent antibodies against brain-spe cific proteins or against a variety of viral agents causing CNS infections [30]. In multiple sclerosis the oligoclonal bands are unidentified but, for example, in HSV enceph alitis the bands at least partly represent herpesvirus-spe cific antibodies [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of CSF immunoglobulin levels and oligoclonal bands, a measure of abnormal IgG produc-tion against a variety of viruses [28], have shown contradictory results. In comparison to a control group in which none of these proteins was isolated, Ahokas et a1 [29] reported the presence of oligoclonal bands in 36% of a sample of patients with schizophrenia and 50% of patients with "reactive" psychosis.…”
Section: The Viral Hypothesis Of Schizophreniamentioning
confidence: 99%